2019
DOI: 10.3390/math7070623
|View full text |Cite
|
Sign up to set email alerts
|

The Forex Trading System for Speculation with Constant Magnitude of Unit Return

Abstract: The main purpose of this article is to investigate a speculative trading system with a constant magnitude of return rate. We consider speculative operations related to the exchange rate given as the quotient of the base exchange medium by the quoted currency. An exchange medium is understood as any currency or any precious metal. The unit return is defined as the return expressed in the quoted currency by the amount of base exchange medium. All possible states of the exchange market form a finite elemental spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 20 publications
0
21
0
5
Order By: Relevance
“…Moreover, the F-PV estimation should be supplemented by a forecast of price closest changes. For example, price closes changes may be predicted with the use of prediction table presented in [125]. In [126], it is shown that OFN application for a portfolio analysis is more useful than the analogous application of FN.…”
Section: Oriented Fuzzy Present Valuementioning
confidence: 99%
“…Moreover, the F-PV estimation should be supplemented by a forecast of price closest changes. For example, price closes changes may be predicted with the use of prediction table presented in [125]. In [126], it is shown that OFN application for a portfolio analysis is more useful than the analogous application of FN.…”
Section: Oriented Fuzzy Present Valuementioning
confidence: 99%
“…These price changes may be subjectively predicted. Moreover, closest price changes may be predicted with the help of the prediction tables presented in [82]. For these reasons, an imprecise PV should be evaluated by OFN [7,70].…”
Section: Oriented Present Valuementioning
confidence: 99%
“…In case of a more probable increase, the TP level describes a change of a value 1, and SL describes the occurrence of 0 (contrary to the case of a more probable decrease). In this case, the probability distribution of the future change direction is equal to the probability distribution of profits (Piasecki and Stasiak 2019). Example 5 corresponds with the Example 3 and presents the differences in application possibilities of the research results based on the candlestick and binary representation, respectively.…”
Section: Application Of the Binary-temporal Representationmentioning
confidence: 99%